Guardians of Health: Vaccines in the Battle Against Communicable Diseases Protecting the Vulnerable: Vaccines in Humanitarian Context - Ismail, Zulkifli; Balasundaram, Susheela; Megat Hashim, Megat Mohamad Amirul Amzar Bin (International Journal of Human and Health Sciences (IJHHS), 2025)
The history of vaccination in Malaysia dates back from 1950. The increase in number of antigens in our immunisation schedule exceeds many other neighbouring countries and some developed nations. The effects on vaccine preventable diseases have also been dramatic with decreases in measles, congenital rubella syndrome, hepatitis B, and the eradication of smallpox in 1980. Vaccine confidence remains the greatest challenge to the National Immunisation Programme (NIP). The number of vaccine hesitancy and refusal in MOH Health Clinics has gone up from a baseline of about 1.5 to 3.2 per thousand live births to 6.7 in 2023. In vaccinology, there is no room for error in one vaccine that can trigger a cascading domino effect on the uptake of childhood vaccines especially, as seen in the Philippines with the first dengue vaccine. The challenges to our highly successful immunisation programme are many and most are related to misinformation and disinformation on social media. We can expect more antigens to be introduced in our NIP but our healthcare system and NGOs should be positioned to support vaccination in social media and other platforms. There should be many more pro-vaccination influencers to counter the many anti-vaccination narratives. Healthcare Professionals (HCPs) should be (and be seen to be) supporting vaccination from their example, actions and words. We know that vaccination saves lives, we just need to disseminate that to the public. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S20